2018
DOI: 10.1155/2018/7108215
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Arterial Air Embolism after Diagnostic Flexible Fiberoptic Bronchoscopy: A Case Report and Review of the Literature

Abstract: Cerebral arterial air embolism (CAAE) is an extremely rare complication of diagnostic flexible fiberoptic bronchoscopy, reported to occur once about every 103978 examinations. In all the eight cases of CAAE reported previously, the patients had undergone transbronchial lung biopsy (TBLB) or transbronchial needle aspiration (TBNA) prior to the onset of CAAE. Herein, we describe the case of a 77-year-old patient with double primary lung cancer who developed CAAE after bronchial curette cytology, which is conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 13 publications
2
13
1
Order By: Relevance
“…What they found was consistent with the fact that high ow of coolant gas can lead to vascular air embolism during the use of contact probe [10]. Other possible risk factors for CAAE include patients with chronic obstructive pulmonary disease, a cavity inside the mass, lesions in the upper lobe, left lateral position, semi-recumbent position and bleeding [1,7,18].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…What they found was consistent with the fact that high ow of coolant gas can lead to vascular air embolism during the use of contact probe [10]. Other possible risk factors for CAAE include patients with chronic obstructive pulmonary disease, a cavity inside the mass, lesions in the upper lobe, left lateral position, semi-recumbent position and bleeding [1,7,18].…”
Section: Discussionsupporting
confidence: 64%
“…Hyperbaric oxygen therapy is recommended as the most bene cial treatment of CAAE [9,[16][17][18]20]. The mechanisms of hyperbaric oxygen therapy for CAAE include: reduced air volume, increased diffusion gradient out of the bubbles, reduction in cerebral edema, decreased endothelial damage, promotion of restoration of distal blood ow [3,6,16,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an animal study, Feller-Kopman et al [ 10 , 13 ] found that bronchoscopic thermal ablation with gas flow is associated with the occurrence of gas embolism in a dose-dependent manner, which is consistent with the fact that high flow of coolant gas can lead to vascular air embolism during the use of a contact probe [ 10 ]. Other possible risk factors for CAAE include patients with chronic obstructive pulmonary disease, a cavity inside the mass, lesions in the upper lobe, left lateral position, semi-recumbent position and bleeding [ 1 , 7 , 18 ]. In this case, the tumour was located in the posterior segment of the right upper lobe, completely obstructing the bronchus.…”
Section: Discussionmentioning
confidence: 99%